Meningkatkan Minat Siswa Laki-Laki melaluiPemilihan Materi Gerak Tari dalam Kegiatan Pengembangan Diri Di Smp Negeri 29 Padang - Bening Herfa Sucia; Fuji Astuti; Zora Iriani (SENDRATASIK UNP, 2015)
Abstract This article aims to reveal and describe the dance movement material selection can improve male student interest in self-development activities. This type of research is qualitative research. This research instrument is the researchers themselves with the respondent that in SMP 29 Padang, another research data collected using field notes, observations were observed by peers. Research data collection is done by literature study, observation, interviews and documentation. Data were analyzed by percentage formula. From the research results can be explained that before the teacher of Arts and Culture using election material appropriate dance movement in the learning process of male students seem indifferent in receiving dance. After the teacher of using election material Cultural Arts dance right in the process of self-development activities of interest of male students at SMPN 29 Padang on particular subjects Cultural Arts Dance increases. At the time of school hours students will do the teachers demonstrated motion, it can be seen from the meetings I to V desire (36%), concern (43%), and participation (38%) of students has been an increase, in this case the observation of increasing student interest men enter into the good category (66.7%)   Keywords: Increasing interest in boys, the selection of materials, self-development.